How full am I? The effect of rating fullness during eating on food intake, eating speed and relationship with satiety responsiveness. (1st February 2021) - Hinton, Elanor C.; Leary, Sam D.; Comlek, Latife; Rogers, Peter J.; Hamilton-Shield, Julian P.
Abstract: Modifying eating behaviours may be an effective strategy to limit excess food intake, such as eating slower and mindfully. We hypothesized that regularly rating fullness whilst eating a standard meal in one course would increase post-meal satiety and reduce intake in a subsequent course during the same sitting. A between-subjects design was employed (n = 65; 75% female; mean age = 26.7 (s.d. = 9.5); mean body mass index = 22.4 (s.d. = 3.3)), with three conditions of within-meal visual-analogue-scale ratings: 'Fullness' (rated fullness); 'Taste' (rated pleasantness of taste of food); 'Control' (rated comfort of room). Fasted participants ate a pasta meal (327 kcal) followed by cookies ad libitum . Appetite ratings were measured at baseline, following each course and for 3-h post-meal. Satiety responsiveness was measured using the Adult Eating Behaviour Questionnaire, Intuitive Eating Scale and by calculating the satiety quotient of the pasta course alone and the whole meal. The primary outcomes were fullness ratings post-pasta course [mean (s.d.): Fullness = 67.1 (21.9); Taste = 64.4 (13.7); Control = 60.2 (21.5)] and cookie intake [mean kcal (s.d.): Fullness = 249 (236); Taste = 279 (231); Control = 255 (208)]. Eating speed was included as a secondary, control outcome [mean (s.d.): Fullness = 59.3 (9.0); Taste = 59.2 (17.7); Control = 60.7 (19.6)]. No evidence for a difference in outcomes was identified between conditions (p > 0.05). Future work could involve testing the impact of rating fullness during multiple meals over a longer period. Secondly, this study explored whether levels of satiety responsiveness influenced the impact of the manipulation on outcomes; however only weak evidence for a relationship with eating speed was found. Finally, only a weak relationship was found between the satiety responsiveness measures, suggesting that different aspects of the underlying construct are being captured.